PEMBELAJARAN TEMATIK DI SEKOLAH DASAR : Literature Riview - Faqih Hakim Hasibuan; Dira Puspita Sari (CV. Adiba Aisha Amira, 2023)
English abstracts made between 150-200 words contain goals, problems, metho;ds, and results. Abstracts are written using the 12-size garamond, spaced 1 and with a text length between 150-200 words. The English version of the abstract is written using standard English with enhanced spelling, protruding left and right 1 cm. This research was conducted to determine the implementation of thematic learning in elementary schools. The method used in this research is to use a literature study or to search by collecting relevant theoretical references from the cases of the problems found. Literature study in general is a way to solve a problem by finding and exploring existing or previously made sources. Based on the review conducted, it was found that there were significant differences in the implementation of thematic learning in elementary schools. There are implementations of thematic learning that have been implemented well and some that have not been implemented properly, so it can be concluded that the implementation of thematic learning in elementary schools is still not implemented properly or not optimal. Because of the obstacles experienced by the teacher and there is still a lack of understanding of the teacher in carrying out thematic learning.